2015
DOI: 10.1155/2015/917968
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin Receptor Based Imaging and Radionuclide Therapy

Abstract: Somatostatin (SST) receptors (SSTRs) belong to the typical 7-transmembrane domain family of G-protein-coupled receptors. Five distinct subtypes (termed SSTR1-5) have been identified, with SSTR2 showing the highest affinity for natural SST and synthetic SST analogs. Most neuroendocrine tumors (NETs) have high expression levels of SSTRs, which opens the possibility for tumor imaging and therapy with radiolabeled SST analogs. A number of tracers have been developed for the diagnosis, staging, and treatment of NET… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 102 publications
0
28
0
Order By: Relevance
“…Neuroendocrine tumors (NETs) overexpress SSTRs, which provides a molecular basis for tumor imaging and therapeutic interventions with somatostatin analogs (SSAs) (9,10). Firstgeneration SSAs, octreotide and lanreotide, are approved for carcinoid symptom control as well as for antitumor activity in metastatic NETs (11).…”
Section: Somatostatin Receptor Expression Is Associated With Metastasmentioning
confidence: 99%
“…Neuroendocrine tumors (NETs) overexpress SSTRs, which provides a molecular basis for tumor imaging and therapeutic interventions with somatostatin analogs (SSAs) (9,10). Firstgeneration SSAs, octreotide and lanreotide, are approved for carcinoid symptom control as well as for antitumor activity in metastatic NETs (11).…”
Section: Somatostatin Receptor Expression Is Associated With Metastasmentioning
confidence: 99%
“…The most commonly applied is the SSTR-ligand [ 111 In-DTPA 0 ]octreotide, which is used for diagnosis and staging. Tumors being positively marked by [ 111 In-DTPA 0 ]octreotide can be treated subsequently with SSTR-ligand bound therapeutic radionuclides, such as [ 90 Y-DOTA0-Tyr 3 ]octreotide ( 90 Y-DOTATOC) and [ 177 Lu-DOTA0-Tyr 3 ]octreotate [ 20 – 22 ]. Such combinations of diagnostically- and therapeutically-labeled molecules are often called “theranostic twins” [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that yttrium may be more effective for larger masses, whereas lutetium may be better suited for smaller lesions. 51 Lutetium-177-DOTA-octreotate is the only compound to have been tested in a phase 3 trial. In this study, the agent was associated with a significant improvement in progression-free survival (p < 0.001), but only a modest fraction of patients demonstrated objective tumor response.…”
Section: Medical Therapiesmentioning
confidence: 99%